Library Best Practices Expert System (LIBPES): Proposal for a Conceptual Prototype - Deshpande, Bhalachandra S.; Sajana, C. (Journal of Information and Knowledge, 2021)
Artificial Intelligence (AI) concepts and technologies can assist Library Professionals in Library management by providing information support systems such as Recommendation Systems, Expert Systems (ES), and Decision Support Systems. This paper proposes the application of AI in Library and information practice through an Expert System for Library management namely Library Best Practices Expert System (LIBPES). The proposed approach is expected to provide situation specific advice based on user (Library Professional) input and requests using case specific data from Five Laws of Library Science, LIS Expert suggestions and various Library Standards, theories, guidelines and principles. The detailed architecture of the proposed expert system and the various User Interface modules are described. While there is some literature on the use of expert systems in libraries, there is no work on giving an all-inclusive search result to the decision maker. Hence, the proposed system can be a basic companion to any Librarian or a library policy maker for overall Library management and decision making.